(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Hierarchical structure and argument structure along with widely studied properties of natural language are paramount This article provides the aspects of language from a range of perspectives, touching on a number of fundamental issues, notably the word structure and variation in subject properties across languages.